Establishment of Kampoeng ASI in Jatimulyo Village, Kebumen - Eka Riyanti; Nurlaila Nurlaila; Yuli Susilowati; Siti Nur Khazanah; Tri Indah Lestari; Annisa Batrisya Irdina; Anama Hilda Aulia (Community Empowerment, 2022)
For babies aged 0 to 6 months, the best food is mother's milk. Mothers who do not exclusively breastfeed are at risk of bleeding and breast cancer. Likewise, babies who are not exclusively breastfed are more susceptible to illnesses like fever, cough, runny nose, and diarrhea. The purpose of community service is the establishment of “Kampoeng ASI” in Jatimulyo Village. This program method entails the training and mentoring of ASI cadres (basic communication, counseling, exclusive breastfeeding, and proper breastfeeding techniques) for pregnant women and breastfeeding mothers. A pre-post test was used to assess ASI cadres' knowledge. The results revealed an increase in Jatimulyo ASI cadres' knowledge and ability in communication, breastfeeding counseling, and breastfeeding practices. The plan for this activity's follow-up is for ASI cadres to participate in breastfeeding campaigns with villages and puskesmas on a regular basis. The establishment of "Kampoeng ASI" resulted in the selection of 15 ASI cadres as well as the availability of breastfeeding counseling media.